2010
DOI: 10.1063/1.3353991
|View full text |Cite
|
Sign up to set email alerts
|

Impact of in situ oxygen plasma cleaning on the resistance of Ru and Au-Ru based rf microelectromechanical system contacts in vacuum

Abstract: Contact resistance measurements are reported for radio frequency microelectromechanical system switches operating in an ultrahigh vacuum system equipped with in situ oxygen plasma cleaning capabilities. Ru-based contacts were prepared by means of standard sputtering techniques, sputtering followed by postdeposition oxidation, ͑surface RuO 2 ͒ or reactive sputtering in the presence of oxygen ͑bulk RuO 2 ͒. In situ oxygen plasma cleaning lowered the resistance of Ru contacts by two or more orders of magnitude bu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

4
32
0

Year Published

2011
2011
2019
2019

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 44 publications
(36 citation statements)
references
References 29 publications
4
32
0
Order By: Relevance
“…The system is equipped with in situ oxygen plasma cleaning capabilities and has the ability to immediately expose the samples to partial pressures of dodecane gas, or alternatively examine samples lifetimes in either vacuum or nitrogen environments. In this stringently controlled chamber, we have previously reported the baseline contact resistance values after cleaning to be close to those theoretically predicted for a contact with no adsorbed contaminant film [8]. Au-RuO 2 contacts were selected for our studies, as they are a promising materials combination for RFMEMS devices [8,37], and in particular remain operational in a wide range of conditions so as to allow controlled studies to be performed on them [8].…”
mentioning
confidence: 92%
See 3 more Smart Citations
“…The system is equipped with in situ oxygen plasma cleaning capabilities and has the ability to immediately expose the samples to partial pressures of dodecane gas, or alternatively examine samples lifetimes in either vacuum or nitrogen environments. In this stringently controlled chamber, we have previously reported the baseline contact resistance values after cleaning to be close to those theoretically predicted for a contact with no adsorbed contaminant film [8]. Au-RuO 2 contacts were selected for our studies, as they are a promising materials combination for RFMEMS devices [8,37], and in particular remain operational in a wide range of conditions so as to allow controlled studies to be performed on them [8].…”
mentioning
confidence: 92%
“…Walker et al [8], for example, reported contaminant films to reform after several days in UHV, and almost immediately in highvacuum conditions. Such contaminant layers are generally invoked whenever experimentally measured resistances are found to be higher than theoretical values for a clean contact [4,8]. The situation is complicated, however, by the fact that actual contact occurs only at a limited number of small ''contact spots'' [24][25][26] that can exhibit asperity creep and grow larger in time [27][28][29][30].…”
mentioning
confidence: 96%
See 2 more Smart Citations
“…Ru films are deposited on the movable electrode, and also on a part of the substrate, and are characterized by a thickness t s and a Young modulus E s . Typical value for the Ru film thickness is reported in Table 2 [52], and the Young modulus is the one reported in Table 1.…”
Section: Application To a 1d Micro-switchmentioning
confidence: 99%